Design of a high-efficiency Class D amplifier for ceramic speakers - Hu, Hui. (2013)
This report documents the motivation, methodology and results analysis of design a Class D amplifier for ceramic speakers. In this final year project, both dynamic speaker and ceramic speaker’s properties were examined and analyzed, and a Class D amplifier was designed as an audio amplifier. It was reviewed that ceramic speaker is more than 60 % smaller in size and more acoustical efficient at frequency spectrum from 1 kHz to 8 kHz, but requires a higher supply voltage which is around 15 Vp-p, while dynamic speakers need only around 2-5 Vp-p. Hence ceramic speaker is the future trend in sound producing device.